Assessing the Distributive Effects of Minimum Wage - Fernando Borraz; González Pampillón (Global Labor Organization (GLO), 2017)
This paper analyzes the role of Uruguay's sharp minimum wage increases after 2004 amidst the country's slight wage inequality decrease. We found that the minimum wage increase has contributed to the reduction of wage inequality for formal workers mainly. However, we also found a negative impact on employment outside the capital city, Montevideo, and observed a reduction in working hours. These results raise doubts about the effectiveness of minimum wage as a redistribution instrument in developing countries.
Keywords: J20; J31; J38; 330; minimum wage; wage inequality; instrumental variables; employment effect; difference in difference